Effect of lattice mismatch and shell thickness on strain in core@shell nanocrystals. Issue 3 (2nd March 2020) - Gamler, Jocelyn T. L.; Leonardi, Alberto; Sang, Xiahan; Koczkur, Kallum M.; Unocic, Raymond R.; Engel, Michael; Skrabalak, Sara E.
Abstract : Bimetallic nanocrystals with core@shell architectures are versatile particles. Geometric phase analysis of TEM images and atomistic simulations are coupled to reveal the lattice relaxation as a function of lattice mismatch and shell thickness. Abstract : Bimetallic nanocrystals with a core@shell architecture are versatile, multifunctional particles. The lattice mismatch between core and shell regions induces strain, affecting the electronic properties of the shell metal, which is important for applications in catalysis. Here, we analyze this strain in core@shell nanocubes as a function of lattice mismatch and shell thickness. Coupling geometric phase analysis from atomic resolution scanning transmission electron microscopy images with molecular dynamics simulations reveals lattice relaxation in the shell within only a few monolayers and an overexpansion in the axial direction. Interestingly, many works report core@shell metal nanocatalysts with optimum performance at greater shell thicknesses. Our findings suggest that not strain alone but secondary factors, such as structural defects or structural changes in operando, may account for observed enhancements in some strain-engineered nanocatalysts; e.g., Rh@Pt nanocubes for formic acid electrooxidation.